URGENSI PENGUATAN PERAN DAN FUNGSI BADAN PERMUSYAWARATAN DESA DALAM PERSPEKTIF DEMOKRASI (STUDI BPD DESA KARYAMULYASARI KECAMATAN CANDIPURO LAMPUNG SELATAN) - Muhtadli Muhtadli (Muhammadiyah Law Review Journal, 2018)
This research discusses the urgency of strengthening the role and function of the Village Consultative Body in a democratic perspective. The method used in this study is a normative juridical approach to literature and legislation, as well as a historical approach. The conclusions obtained from this research are that the Village Consultative Body is currently no longer an element of village administration and a partner of the Village Head in the affairs of village administration and is outside the government structure, the two functions of the Village Consultative Body carry out a supervisory function as the main function, while the legislative function become a function of the village government. Therefore, it is urgent to strengthen the role and function of the BPD as an instrument in carrying out checks and balances so that the implementation of village governance runs democratically.